The levels of IFN- , IL-12 And Testosterone Hormone in Persons with Asymptomatic Toxoplasmosis - Abdul-Lateef, Huda I.; AL-Najar, Sabah A.; Abul Majeed, Nahla G. (Journal of the Faculty of Medicine Baghdad, 2012)
Background: The primary goal of this study is to perceive the immunological differences in mean level of IFN- and IL-12 in persons who have positive results for anti-toxoplasma gondii antibodies compared to persons who gave negative results for these antibodies. The secondary goal is to inspect the endocrineimmune interaction in thesepersons by detecting the effect of testosterone hormone level on cellular immune response namely, IL-12& IFN- . This study also detect the effect of Toxoplasma gondii on the level of testosterone hormone in those persons compared with healthy control. Objective: Investigate the relationship between T. gondii and serum IL-12,IFN- and testosterone hormone levels in asymptomatic persons with positive anti-toxoplasma antibodies compared with healthy control and Study the endocrine _immune interaction in these persons . Patients and methods: Seventy seven asymptomatic persons who have positive anti-toxoplasma antibodies and 30 persons who have negative anti-toxoplasma antibodies were included in this study and subjected to estimating the levels of IL-12, IFN- and testosterone hormone by ELISA technique. Results: The levels of both IL-12 and IFN- were statistically higher in persons with positive antitoxoplasma antibodies than in control. The levels of testosterone hormone were higher in both males and females with positive toxoplasmosis than control. There was a positive association between increased level of testosterone and IL-12 level while there was no effectiveness of testosterone on IFN- level in persons with positive anti-toxoplasma antibodies. Conclusion: Toxoplasma gondii elicits cellular immune response detected by statistically important increased in IL-12 and IFN- level compared with control. Not only host hormone can affect responses to infection, but parasites can both enhance production and alter hormone concentration in their hosts.